The Syntax of Old Catalan Clitics: “Llibre dels Fets” - Andreu Sentí; Miriam Bouzouita (Catalan Journal of Linguistics, 2022)
Although the distribution of pronominal clitics in Old Catalan has been described in general terms (Fischer 2002; Batllori et al. 2005), there are no quantitative studies detailing the frequency of preverbal or postverbal clitics nor their diachronic evolution. The clitics appearing with verbs in the future and conditional tense (FC) are worth a separate mention, since these forms originate from periphrastic structures that involve an infinitive and the auxiliary verb habere, and which could appear as an analytic (dir-li he) or a synthetic form (li diré or diré-li). This paper describes the general clitic positioning and the one encountered with FC in order to verify the claim that they display parallel distributions, using a text from the 13th century, to wit Llibre dels Fets. This article analyses the pragmatic-syntactic environments in which the clitic are found, as well as the degree of grammaticalization and univerbation of the FC. Following previous work (e.g., Bouzouita & Sentí 2022), it is argued that the FC in Catalan appear to exhibit a more advanced degree of grammaticalization than the western languages of the Iberian Peninsula.